Reoperation for intracranial hypertension in TWIST1-confirmed Saethre-Chotzen syndrome: a 15-year review. - Woods, R; Ul-Haq, E; Wilkie, A; Jayamohan, J; Richards, P; Johnson, D; Lester, T; Wall, SA (2009)
BACKGROUND: Saethre-Chotzen syndrome is a syndromic craniosynostosis defined by a genetic mutation affecting the TWIST1 gene on chromosome 7p21. It is typically associated with unicoronal or bicoronal synostosis, eyelid ptosis, dysmorphic external ears, and other variable facial and limb abnormalities. Surgical management of the craniosynostosis addresses the calvarial deformity and may relieve or reduce the risk of intracranial hypertension. The aim of this study was to assess surgical intervention, with particular consideration of the reoperation rate for intracranial hypertension, in Saethre-Chotzen syndrome patients. METHODS: A retrospective case note analysis was performed on all patients with a confirmed TWIST1 gene abnormality who attended the Oxford Craniofacial Unit over a 15-year period. Each patient's mutation and clinical features were recorded. Surgical intervention and sequelae were examined in greater detail. RESULTS: Thirty-four patients with genetically confirmed Saethre-Chotzen syndrome were identified. All had craniosynostosis (bicoronal, 76 percent; unicoronal, 18 percent; bicoronal and sagittal, 6 percent), and the majority had eyelid ptosis, low frontal hairline, and external ear anomalies. Thirty-one patients had received surgical intervention. Nine of 26 patients (35 percent) with at least 12 months of follow-up after primary intervention and eight of 19 patients (42 percent) with at least 5 years of follow-up developed intracranial hypertension necessitating secondary calvarial surgery. CONCLUSIONS: Despite standard surgical intervention, patients with Saethre-Chotzen syndrome have a high rate (35 to 42 percent) of recurrent intracranial hypertension necessitating further surgical expansion. All patients with either bicoronal synostosis or unicoronal synostosis with syndromic features should be screened for TWIST1 mutations, as this confers a greater risk than nonsyndromic synostosis of the same sutures. Regular follow-up throughout the childhood years is essential.